In a long-winded road: Understanding the lived experiences of faculty members on module writing in the new normal - Roselle Matammu Soriano; Kristine Bernadette M. Apolonio; Carmela Gandia Blando (Institute of Advanced Engineering and Science, 2022)
The COVID-19 pandemic has caused unprecedented difficulties and obstacles for educational sectors, with no one knowing when it will end. The number of illnesses continued to rise while countries worldwide established plans and processes to limit the virus. To maintain and deliver a high-quality education notwithstanding community quarantine, the new normal should be incorporated into the formulation and implementation of the